Precision Redefined: A Narrative Review of Implant Guiding System - Dr. Sapam Shinttoo Devi; Dr. Shalabh Kumar; Dr. Rohit Nandan; Dr. Susheel Kumar Khera; Dr. Susheel Kumar Khera; Dr. Meghna Choudhury; Dr. N. Sai Charan Deepak Rao (The Bioscan, 2026)
The implantation of dental implants is one of the most famous choices for patients who are missing teeth. Dental implants are becoming increasingly common, so it is crucial to place them precisely to prevent them from failing. Surgical guides are essential for transferring the digitally planned treatment regimen to the actual surgical sites and for achieving accuracy during implant planning and placement. Surgical guides for implants are defined and discussed in this article, along with their functions, types, and benefits.